How do foreign language teachers motivate students in language learning? - Diana S Rahman; Wening Sahayu (Studies in English Language and Education, 2020)
Motivation is one of the keys to success in the language learning process. It is a crucial factor for students in learning a foreign language, and the teachers’ ways to motivate students are also essential. This study aims to investigate language teachers’ ways in motivating students in learning foreign languages. The participants in this study are eight foreign language teachers including English, Arabic, and French teachers. Data were collected through open-ended questionnaires with the teachers. The results of this study showed that most of the foreign language teachers motivated the students in learning a foreign language by sentences (verbal) and this method encouraged students’ instrumental motivation. Next, referring to the time of motivation, four teachers motivated the students at the beginning of each learning process, meanwhile three teachers gave motivations at the beginning and at the end of each learning process. Finally, referring to the types of motivation, only two teachers (i.e. French teachers) could identify motivation types of learners, which are in the form of internal, external, intrinsic, and extrinsic motivation. Meanwhile, other teachers (i.e. English and Arabic teachers), did not mention specifically the names of the motivation types that they knew. To conclude, most of the teachers of this study did not motivate their students maximally in the classrooms. Consequently, this study offers some methods to motivate learners in learning foreign languages, those are the Verbal Method (VM1) and the Visual Method (VM2), and they are further discussed in the paper.